Excessive use of artificial intelligence in accounting undergraduate courses: risks of technological dependence on the development of analytical skills - Guedes, Kayllanne Karla Gomes; Vasconcelos, Ana Lúcia Fontes de Souza; Abreu, Rute; Henriques, Caio Arruda Souza; Araújo, Ruth Fonseca de (REVISTA AMBIENTE CONTÁBIL - Universidade Federal do Rio Grande do Norte - ISSN 2176-9036, 2026)
Purpose: To analyze students´ and lectures’ perceptions about the effects of the excessive use of Generative Artificial Intelligence among students enrolled in the Bachelor's Degree in Accounting Sciences at a public higher education institution. Methodology: A mixed-methods approach was adopted, combining quantitative and qualitative procedures. The quantitative approach was administered through structured questionnaires to 204 Accounting students, enabling the measurement of variables and the identification of statistical patterns using Pearson's correlation. The qualitative approach consisted of semi-structured interviews with accounting lectures, allowing and in-depth understanding of subjective perceptions regarding the use of Generative Artificial Intelligence in the teaching-learning process. This methodological combination enabled an integrated and consistent analysis of the impacts of the excessive use of such tools on academic training and the development of analytical skills essential to accounting practice. Results: The analysis revealed significant associations between variables, including between the frequency of use of Generative Artificial Intelligence and the perceived impairment of intellectual autonomy, autonomy and risk to professional education, as well as between analytical reasoning and risk to professional education. Negative correlations were also observed between the clarity of institutional guidelines and variables such as autonomy, analytical reasoning and professional education. The interviews highlighted lecturers’ concerns regarding superficial learning and the loss of critical skills among students. Study Contributions: The findings highlight the risks associated with the excessive use of Generative Artificial Intelligence tools, highlighting that, although they have the potential to support the learning process, their indiscriminate use can compromise the development of fundamental skills for accounting practice, requiring pedagogical interventions that encourage the conscious, critical, and responsible use of Artificial Intelligence within the university environment.